The Metabolism of Hormones during Seed Germination and Dormancy - Sondheimer, Ernest (Plant Physiol, 1971)
8-(14)C-Zeatin is taken up rapidly and is extensively metabolized by excised bean axes during a 12-hour incubation at 26 C. Most of the radioactivity is found in the 80% ethanol soluble fraction and consists of zeatin, zeatin riboside, zeatin-5′-ribotide, as well as corresponding dihydrozeatin derivatives. The characterization of (14)C-dihydrozeatin included crystallization to constant specific radioactivity. No cleavage of the zeatin side chain to adenine, hypoxanthine, their ribosides, or glycylpurine was detected. Dihydrozeatin has been previously isolated from yellow lupin seeds, and our experiments indicate that it can be derived through reduction of the side chain from preexisting cytokinin. While the total amount of zeatin metabolized is not affected by growth-inhibiting concentrations of abscisic acid or cycloheximide, the conversion to dihydrozeatin derivatives is curtailed. Although somewhat less effective than zeatin and zeatin riboside, dihydrozeatin and dihydrozeatin riboside also counteract the abscisic acid-induced growth inhibition.